Identifikasi Risiko Rantai Pasok Bawang Merah di Kabupaten Nganjuk - Susanawati, Susanawati; Jamhari, Jamhari; Masyhuri, Masyhuri; Darwanto, Dwidjono Hadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
This study was conducted in Nganjuk Regency in the reason that this region is the second largest shallot production centre in Indonesia after Brebes Regency. Around 40 percent of shallot from Nganjuk are marketed to Jakarta including Kramatjati Central Market of Jakarta (KCMJ), therefore this study aims to determine actor of the shallot supply chain from Nganjuk to Jakarta and identify the type of risk in the shallot supply chain. The respondents were expert from goverment representatives , academician, and actors of the shallot supply chain. The Analytical Hierarchy Process (AHP) model was used to identify risk of the shallot supply chain. The result showed that there were seven actors involved in the shallot supply chain from Nganjuk to Jakarta, namely farmer, buyer, wholeseller, bandar, centheng, retailer, and consumer. The AHP model showed that risk of market was the main risk in the shallot supply chain from Nganjuk to Jakarta, following by risk of partnerships and information, and price risk.